Software configuration management patterns : effective teamwork, practical integration - Berczuk, Stephen P. (Software patterns series., 2003)
Stereotypes portray software engineers as a reckless lot, and stereotypes paint software configuration management (SCM) devotees as inflexible. Based on these impressions, it is no wonder that projects can be riddled with tension! The truth probably lies somewhere in between these stereotypes, and this book shows how proven SCM practices can foster a healthy team-oriented culture that produces better software. The authors show that workflow, when properly managed, can avert delays, morale problems, and cost overruns. A patterns approach (proven solutions to recurring problems) is outlined so that SCM can be easily applied and successfully leveraged in small to medium sized organizations. The patterns are presented with an emphasis on practicality. The results speak for themselves: improved processes and a motivated workforce that synergize to produce better quality software.